2013
DOI: 10.5455/2319-2003.ijbcp20130317
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ART adverse reactions and determinants at primary hospital in Ethiopia

Abstract: Background: Much progress has been made in treating HIV infection in the last several years and currently antiretroviral therapy regimens are capable of reducing viral load of undetectable level with a consequent increase in T-lymphocyte, CD4+ counts and reduction in development of opportunistic infections. Hence, a substantial reduction in HIV associated morbidity and mortality can be attained. In spite of antiretroviral therapy benefits, adverse reaction to these drugs has been pointed to as one of the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…However, higher prevalence rate of 71.7% was observed in female married patients. These results are supported by the study conducted in Ethiopia [21]. The reason may be that majority of the HIV infected female patients were married.…”
Section: Discussionsupporting
confidence: 80%
“…However, higher prevalence rate of 71.7% was observed in female married patients. These results are supported by the study conducted in Ethiopia [21]. The reason may be that majority of the HIV infected female patients were married.…”
Section: Discussionsupporting
confidence: 80%
“…35 This may because of exclusion of mild ADRs may be contributory to the low ADR in the study done in India, but lower when compare to study done in Ambo zonal hospital 36 is 81.5%. There is another assessment of adherence to ARV therapy at the Ministry of National Defense Force hospitals showed that 54.0% developed mild ADRs, 37 it is also less than our study results.…”
Section: Discussionmentioning
confidence: 67%
“…The sample size for the study was determined based on patients taking ART develop ADRs from research done in Ambo zonal hospital. 32 Taking critical value at 95% confidence level, degree of precision 0.05, missing or incomplete record by adding 10% of the contingency (21 patients) minimum actual sample size is 233. Every 10th patient's clinical record is included in the sample.…”
Section: Sampling Size and Study Variablesmentioning
confidence: 99%
“…16,17 However, the prevalence rate reported in this study is higher than the report from Ambo referral hospital, Ethiopia, which is 35.7%. 8 This difference might be because the study in Ambo referral hospital included patients who took ART for more than 6 months, obtained data from patient charts only and included patients on non-EFV-based ART regimens. The most commonly reported CNS adverse events in our study were vivid dreams (29.9%), confusion (27.5%), insomnia (24.1%) and somnolence/drowsiness (20.9%).…”
Section: Discussionmentioning
confidence: 99%